Rural Emergency Laparotomy Audit. Issue 6 (13th May 2019) - Watson, Matthew M.; Maddern, Guy J.; Mudalige, V. Priyantha K.; Pradhan, Chetan P.; Wichmann, Matthias W.
Abstract : Background: Emergency laparoscopy/laparotomy is associated with high levels of mortality. The aim of this study was to determine whether outcomes following emergency laparoscopy/laparotomy in rural and regional South Australian hospitals were comparable to those reported in the National Emergency Laparotomy Audit and Perth Emergency Laparotomy Audit. Methods: A prospective multicentre audit of patients who undergo emergency laparoscopy/laparotomy. Participating hospitals included Mount Gambier and Districts Health Service, Whyalla Hospital and Riverland General Hospital. Inclusion and exclusion criteria were identical to the National Emergency Laparotomy Audit. A modified dataset for patients was collected if patients were up‐transferred to another hospital prior to operative management. Data collected included patient demographics, operative management, adherence to processes of care and outcomes. Results: Data were collected for a total of 58 cases. Fifty‐one of these had emergency laparoscopy/laparotomy in a rural or regional hospital and seven were transferred in the preoperative period. The median Portsmouth‐Physiological and Operative Severity Score for the enUmeration of Mortality and Morbidity predicted 30‐day post‐operative mortality was 3.5%. One hundred percent of patients (51 out of 51) had a consultant anaesthetist and surgeon present in the operating theatre. There were no deaths reported within the 30‐day post‐operative period. Conclusion: Outcomes following emergency laparoscopy/laparotomy in rural and regional South Australian hospitals are comparable to those reported in the National Emergency Laparotomy Audit and Perth Emergency Laparotomy Audit. Abstract : Emergency laparoscopy/laparotomy is associated with high levels of mortality. The aim of this multicentre prospective study was to determine whether outcomes following emergency laparoscopy/laparotomy in rural and regional South Australian hospitals were comparable to those reported in the National Emergency Laparotomy Audit and Perth Emergency Laparotomy Audit.